FOXP3 full length splice variant is associated with kidney allograft tolerance - Saleh, Qais W.; Mohammadnejad, Afsaneh; Tepel, Martin (Frontiers in Immunology, 2024)
Background Progressive decline of allograft function leads to premature graft loss. Forkhead box P3 (FOXP3), a characteristic gene of T-regulatory cells, is known to be essential for auto-antigen tolerance. We assessed the hypothesis that low FOXP3 mRNA splice variant levels in peripheral blood cells early after transplantation are associated with progressive allograft injury. Methods Blood samples were prospectively collected from 333 incident kidney transplant recipients on the first and 29th postoperative day. We used quantitative polymerase chain reaction to determine transcripts of 3 isotypes of FOXP3 splice variants, including pre-mature FOXP3 and full length FOXP3 (FOXP3fl). We investigated the association between FOXP3 splice variant levels and the declines in estimated glomerular filtration rate (eGFR) of more than 5ml/min/1.73m2 within the first-year post-transplant using logistic regression. Results We observed lower FOXP3fl levels in recipients with declining eGFR (N = 132) than in recipients with stable eGFR (N = 201), (logarithmic value -4.13 [IQR -4.50 to -3.84] vs -4.00 [ 4.32 to -3.74], p=0.02). In ad hoc analysis pre-transplant FOXP3fl levels were similar in both groups. The association between FOXP3fl and declining eGFR was confirmed by multivariable analysis adjusted for potential confounding factors (Odds Ratio 0.51, 95% confidence interval 0.28 to 0.91: p=0.02). When stratifying FOXP3fl levels into quartiles, recipients with lower day1 FOXP3fl had the highest rate of declining eGFR (p=0.04). Conclusions Low FOXP3fl splice variant levels at the first postoperative day in kidney transplant recipients were associated with severe decline of eGFR, a well-known surrogate for hard endpoints.